FORMATION OF THE RANGE OF MEN’S SHOES TAKING INTO ACCOUNT THE CHARACTERISTICS OF SHAPE AND COLOR ON THE BASIS OF MARKETING RESEARCH - BABYCH, Antonina; GARANINA, Olha; MOSKOVA, Olha (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Colorism and constructivism in the products of the fashion industry, and in particular in shoes, is not a new phenomenon, but it appears more and more often in the works of modern designers, it increasingly affects fashion and the consciousness of consumers thanks to the opportunity to travel and contemplate the world, to study the peculiarities of different cultures subconsciously trying them on. Interesting color and design solutions in shoes give the products functional completeness and expressiveness, and the wearer unique feelings and pleasant impressions. The use of non-standard color and design solutions in the development of shoe models attracts the attention of fashion industry specialists, is traced by a chain of specific actions in the "birth" of an idea, creation of a creative source, sketching, selection of materials and color palette, and in the detailed development of object structures. Development of an assortment of men’s shoes taking into account the features of shape and color due to the use of color accents, compositional and structural elements of shoes. The research used a theoretical-analytical approach to the review and analysis of scientific and technical literature by direction. Marketing research was experimentally conducted to determine the most important forms, functions and color solutions of products in the opinion of consumers, which will make it possible to analyze the results of research and predict a successful and profitable assortment of men’s shoes. The classic designs of men’s shoes have been studied and analyzed. The peculiarities of the technology of manufacturing products, materials, color solutions, innovative techniques, technologies and tools for applying color to materials, individual parts and finished products have been studied. Factors influencing the formation of the assortment of men’s shoes were studied experimentally. The results of marketing research on the possibility of using bold constructive ideas and color solutions in men’s shoes are given. A line of sketches of men’s shoes of various designs using modern constructive and color solutions has been developed, which includes an assessment by experts regarding the relevance of its use in the formation of the assortment and production of products. Samples of shoes were produced and tested. The use of classic and modern non-standard accent color techniques on the finished product for the production of shoes of this segment is predicted, the increase in the manufacturability of the model due to the successful shapes of the parts of the workpiece, the quality of the products as a whole and the increase in demand for shoes by creative Ukrainian designers.